2006
DOI: 10.1002/cbic.200500526
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Structural Investigations on the Torpedo Nicotinic Acetylcholine Receptor by Time‐Resolved Photoaffinity Labeling

Abstract: An increasing number of high-resolution structures of membrane-embedded ion channels (or soluble homologues) have emerged during the last couple of years. The most pressing need now is to understand the complex mechanism underlying ion-channel function. Time-resolved photoaffinity labeling is a suitable tool for investigating the molecular function of membrane proteins, especially when high-resolution structures of related proteins are available. However until now this methodology has only been used on the Tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 110 publications
(155 reference statements)
0
4
0
Order By: Relevance
“…The results indicated that the two substrates should be orientated close together in the active site to promote a conformational change in the enzyme structure 5. Recently it was reported that dynamic structural investigations on the torpedo nicotinic acetylcholine receptor could be performed by time‐resolved photoaffinity labeling 6…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the two substrates should be orientated close together in the active site to promote a conformational change in the enzyme structure 5. Recently it was reported that dynamic structural investigations on the torpedo nicotinic acetylcholine receptor could be performed by time‐resolved photoaffinity labeling 6…”
Section: Introductionmentioning
confidence: 99%
“…Photoaffinity labeling has been used to identify amino acids in the Torpedo nAChR transmitter binding sites (Mourot et al, 2006) and in binding sites for positive and negative allosteric modulators (Nirthanan et al, 2008; Hamouda et al, 2011). Unlike mutational analyses, photoaffinity labeling allows direct identification of residues in a drug binding site (Vodovozova, 2007) and therefore distinguishes amino acids that contribute to a PAM binding site from those involved in allosteric modulation of gating.…”
mentioning
confidence: 99%
“…[7] Besides the resting (closed) and the open state there are also an intermediate (fast onset) and a desensitized (slow onset) state, with the latter resulting from a prolonged overstimulation of the receptor, making it far less susceptible to activation. [3,[7][8][9] It is claimed [9] that these conformational states and their transitions can be influenced by a variety of ligands targeting the orthosteric binding site with acetylcholine [Figure 1; 1] representing the endogenous ligand, or the ion channel pore and other compounds such as positive or negative allosteric modulators (PAMs or NAMs). The affinity of ligands addressing the ion channel distinctly depends on the functional state of the receptor with many ligands showing higher affinity to the desensitized state as shown for antidepressants.…”
Section: Introductionmentioning
confidence: 99%